THE EFEKTIVITAS PEMBERIAN KARTU YU-SB (YUGIOH SAYUR BUAH) SEBAGAI MEDIA PENINGKATAN PENGETAHUAN SAYUR DAN BUAH SISWA SEKOLAH DASAR - AMALINA GITA PUTRI; Irianton Aritonang; Weni Kurdanti (POLTEKKES KEMENKES YOGYAKARTA, 2020)
Background: Consumption of vegetables and fruit is still quite low, at the age of elementary school children is very difficult to be able to eat foods needed for growth. Consumption behavior of vegetables and fruits has a significant relationship one of them with nutritional knowledge, to be able to increase knowledge about nutrition can be done through the process of nutrition counseling. The media needs to be used to increase the target's interest in absorbing information such as YU-SB cards and leaflets. Objective: The purpose of this research was to determine the effectiveness of giving YU-SB cards compared to leaflets as a medium to increase vegetable and fruit knowledge in elementary school students. Method: This type of research is a quasi experiment using pre-posttest with control group design. The research was conducted in January to February 2020. The method of determining the location of the study was carried out by means of purposive sampling, selected fourth grade students of SDN Ngijon I (as a group of YU-SB cards) and fourth grade students of Pendulan SDN (as leaflet groups). Results: The results of the pretest test were not significant p = 0.261 indicating that the initial knowledge of the two groups was the same, the average pretest for the YU-SB card group was 56.50 and the leaflet group was 59.17. The posttest results (p = 0.648) were not statistically significant, but there was a difference in knowledge between the YU-SB card group and leaflets on the posttest results when viewed from an increase in the mean value. The average post-test for the YU-SB card group is 75.00 and the leaflet group is 76.33. There was a significant difference in knowledge before and after counseling with the YU-SB card (p = 0,000) and counseling with leaflets (p = 0,000). Conclusion: The YU-SB card is more effective compared to leaflets as a medium for increasing elementary school students' vegetable and fruit knowledge. Keywords: Media, knowledge of vegetables and fruit, YU-SB card, leaflet